Wideband microstrip-based wearable antenna backed with full ground plane - Ezzaty F. N., Mohd Hussin; Ping, Jack Soh; Mohd Faizal, Jamlos; Herwansyah, Lago; Azremi A., Al-Hadi (John Wiley & Sons, 2019)
A wideband microstrip-based wearable antenna with a fractional bandwidth of 51% is designed using textile materials for wearable applications. The antenna operates between 2 and 3 GHz with low back-radiation to ensure minimum coupling to the body and reduced electromagnetic power absorption in the human tissue. The behavior microstrip antenna topology, which is narrowband in nature, is altered via the combinations of various broadbanding techniques, while maintaining the existence of the full ground plane backing. This ensures that the antenna radiation is directed outward form the body to efficiently propagate wireless signals toward other off-body nodes and base stations. Simulation and measurement results indicated that the use of this microstrip topology with multiple broadbanding techniques is capable of reducing the back lobe, resulting in a front-to-back ratio of about 17 dB and a 3.5 dBi of average gain.